(untitled) (Journal of Organizational Psychology, 2024)
The aim of this study was to assess how students perceive teacher behaviors. The participants, responded to a survey consisting of a short version of the Teacher Behavior Checklist (TBC). The result revealed five dimensions of teacher behavior. We named these dimensions Superlative/Superhuman, Pro-social, Professional, Absent, and Insecure. The positive dimensions, superlative and pro-social had the highest overall rankings, and professional came third. The two negative aspects were behaviors that the students associated with negative teacher behaviors. The analysis revealed differences according to gender as female students rated four of the five dimensions as more important. There were also differences according to educational level. Students at Upper secondary school students rated the pro-social dimension with characteristics, such as, good listener, relation builder and understanding higher. University students had lower tolerance for the absent dimension and stressed the behaviors associated with improving critical thinking skills when compared to the younger sample.